Households' age, country of birth, and marital status, stronger predictor variables than education in the prevalence of dental sealants, restorations, and caries among US children 5-19 years of age, NHANES 2005-2010 - Victor Alos-Rullan (BMC, 2019)
Abstract Background The aim of this study is to use data representative of the U.S. population to determine if households (HHs) age, birth country, and marital status, are strong predictors as HHs education for dental sealants, restorations, and caries in children 5 to 19 years of age. Methods A cross sectional analysis was performed with oral health data from three waves of the National Health and Nutrition Examination Survey (NHANES 2005 to 2010). The sample size consisted of children 5 to 19 years of age (n = 9151) and households > 18 years of age (n = 31,034). Dependent variables included the number of children with dental sealants, restorations, and caries. HHs independent variables consisted of gender, age, race, country of birth, HHs education level, marital status, and HHs spouse education. Multivariate regression analysis models were adjusted for HHs citizenship, health insurance, family size, and children age categories. Results The prevalence of children 5-19 years of age with dental sealants, restorations, and caries was 31.3, 43, and 15.8% respectively. The odds of children having sealants were higher among HHs with a college education or above OR 2.05 [1.54.-2.73] vs. HHs with a < 9th grade, in HHs ages 39-49 (OR 1.78 [1.41-2.24) vs. 18-29 years of age, and in HHs spouses with a college education and above OR 1.71 [1.14-2.56] vs. HHs with a < 9th grade. The odds of having at least one restored tooth were higher in children from HHs born in Mexico 1.74 [1.44-2.10] vs. US born. The highest odds for caries were among children from HHs that were never married 1.91 [1.47-2.48] vs. married HHs. In HHs with a college education the odds for caries in children were 0.31 (0.22-0.43) for college and above, and 0.78 (0.60-1.01) for some college. Conclusions The odds of children having dental sealants were higher in HHs with a college education, however, HHs ages 30-49 provided higher odds for sealants than spouses with college education. HHs birth place increased the odds of children with restorations more than HHs education. Children from HHs that never married had higher odds of experiencing dental caries. Recognizing the impact of these HHs characteristics could augment efforts in the prevention of adverse oral health outcomes in U.S. children. Households' age, country of birth, and marital status, stronger predictor variables than education in the prevalence of dental sealants, restorations, and caries among US children 5-19 years of age, NHANES 2005-2010.